Examining the language and behavioural profile in FTD and ALS-FTD - Saxon, Jennifer A (J Neurol Neurosurg Psychiatry, 2017)
BACKGROUND: A proportion of patients with behavioural variant frontotemporal dementia (bvFTD) develop amyotrophic lateral sclerosis (ALS). It is currently unknown whether the behavioural and cognitive syndrome in bvFTD with ALS (ALS-FTD) is indistinguishable from that of bvFTD alone. METHODS: A retrospective cohort of 241 patients with clinical diagnoses of bvFTD (n=185) or ALS-FTD (n=56) was examined with respect to behavioural, cognitive and neuropsychiatric symptoms. Features were rated as present or absent based on information recorded from clinical interviews and detailed neuropsychological assessment. RESULTS: A number of behavioural and affective changes were reported more frequently in bvFTD than ALS-FTD: social disinhibition (p<0.001), inertia (p<0.001), loss of sympathy and empathy (p=0.008), repetitive behaviours (p<0.001) and dietary changes (p<0.001). Warmth of affect demonstrated in the clinic setting was reported more often in ALS-FTD than bvFTD (p<0.001). Executive impairments occurred equally in both groups. Language impairments were more common in ALS-FTD than bvFTD: agrammatism (p<0.017) and impaired sentence comprehension (p<0.036). Psychotic features were relatively rare and did not distinguish the groups. CONCLUSIONS: Our findings suggest differences between bvFTD and ALS-FTD. In particular, while changes in social behaviour are prominent in bvFTD alone, there may be a comparatively greater degree of language impairment in ALS-FTD. Prospective exploration of the pattern of differences between these groups will be essential. Identification of a distinct neuropsychological phenotype in ALS-FTD may have clinical implications for early diagnosis, disease management and care planning and theoretical implications for our understanding of the relationship between ALS and FTD.